Development of a Communications Strategy for SACAU: Proceedings of the workshop - Hamusimbi, Coillard; Hungwe, Mabel N (FANRPAN, 2004)
The report gives the workshop objectives; challenges and constraints affecting farmer based organizations (FBO) in SADC; and recommendations on how to improve FBO's institutional capacity on policy formulation and analysis, and information dissemination.